Short Communication: Growth and mortality rate of Black Pomfret Parastromateus niger (Bloch, 1795) and Silver Pomfret Pampus argenteus (Euphrasen, 1788) in Paloh Waters, West Kalimantan, Indonesia - ADRIAN DAMORA; DWI ARIYOGAGAUTAMA; RONNY I. WAHJU; HENDRO SUSANTO; JOHN WANG (Society for Indonesian Biodiversity, 2018)
Damora A, Ariyogagautama D, Wahju RI, Susanto H, Wang J. 2018. Short Communication: Growth and mortality rate of Black Pomfret Parastromateus niger (Bloch, 1795) and Silver Pomfret Pampus argenteus (Euphrasen, 1788) in Paloh Waters, West Kalimantan, Indonesia. Biodiversitas 19: 2247-2251. Three species of pomfret fish were caught in Paloh waters including Parastromateus niger, Pampus argenteus, and Pampus chinensis. P. niger and P. argenteus which were more dominant than P. Chinensis. Pomfret fishing in the Paloh waters is not carried out throughout the year, but generally only in August to October every year. The main fishing gear used was drift gill net. Data on the growth parameter and mortality of the pomfret fish is required as an effort for the management of this fish. This study was aimed to estimate the growth and mortality rate of P. niger and P. argenteus in Paloh waters, located in West Kalimantan. This study was conducted from April 2014 to June 2017. The fish samples were collected by catching the fish using drift gill net used by the fishing vessels. The data were analyzed using an analytic model and run using ELEFAN 1 software and Length-converted Catch Curve on FISAT II software. The result showed that von Bertalanffy growth parameters covering growth curvature (k), asymptotic length (L?), and the age of fish in length zero (t0) was 0.26 year-1, 46.2 cm TL and -1.85 years for P. niger and 0.53 year-1, 46.2 cm TL and -0.88 years for P. argenteus. The von Bertalanffy growth function for P. niger as Lt = 46.2[1-e-0.26 (t+1.85)] and for P. argenteus as Lt = 46.2[1-e-0.53 (t+0.88)]. These functions described the expected or average length at a time (age). Total mortality rate (Z), natural mortality rate (M) and fishing mortality (F) were 0.93 year-1, 0.29 year-1 and 0.64 year-1 for P. niger and 1.68 year-1, 0.47 year-1 and 1.21 year-1 for P. argenteus. Exploitation rate (E) was 0.68 year-1 for P. niger and 0.72 year-1 for P. argenteus. The growth of P. niger is slower than the growth of P. argenteus and the fishing mortality of P. argenteus is higher than P. niger’s. Both of the exploitation rates indicated that the fish resources are over-exploited.